Association Between Partner-Relationship Satisfaction During Pregnancy and Maternal Postpartum Depression [39D]. (May 2017) - Mesina, Anna M.; Kjerulff, Kristen H.; Deimling, Timothy; Phaeton, Rebecca; Repke, John T.
Abstract : INTRODUCTION: The purpose of this study was to investigate partner-relationship satisfaction during pregnancy and its association with postpartum depression. Several prenatal risk factors for postpartum depression have been identified, including history of depression, life stressors, and depression during pregnancy. However, little research exists on whether maternal-partner relationship dissatisfaction during pregnancy is associated with increased risk for postpartum depression. METHODS: This was a planned secondary analysis using data prospectively collected from interviews in the third trimester and at 1 month postpartum of women aged 18-35 who delivered their first singleton birth in Pennsylvania, 2009-2011 (N= 2, 844). Relationship satisfaction was measured in the third trimester using items adapted from the Dyadic Adjustment Scale (DAS). Women scoring 12 or greater on the Edinburgh Postnatal Depression Scale (EPDS) at the 1-month interview were categorized as having postpartum depression. Multivariable logistic regression was used to evaluate the association between relationship satisfaction and postpartum depression, controlling for the confounders of marital status, poverty, race/ethnicity, age, history of anxiety/depression, and unintended pregnancy. RESULTS: Women in the lowest third on relationship satisfaction during pregnancy were significantly more likely to score as depressed on the EPDS (odds ratio, 2.14, 95% confidence interval, 1.29-3.55) in comparison to women in the highest third of the distribution, controlling for the confounders. Additional significant predictors were history of anxiety/depression, maternal age younger than 30, and non-white race/ethnicity. CONCLUSION: In this prospective cohort study, we found that low relationship satisfaction during pregnancy was a significant predictor of postpartum depression among first-time mothers.